1976
DOI: 10.1002/bjs.1800630823
|View full text |Cite
|
Sign up to set email alerts
|

The haematological hazards of autotransfusion

Abstract: Fourteen heparinized dogs were autotransfused from 1-5 to 6 times calculated blood volume. Five animals retransfused 12 litres from an intraperitoneal bleed had marked decreases in all cellular elements, haematuria and a large (82 percent) drop in fibrinogen. All these animals died within 12 hours and post-mortem examination revealed evidence of disseminated intravascular coagulopathy. The dogs in which a smaller volume (3-6 litres) was recycled showed similar, but less devastating, changes. Haematocrit and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Al though some investigators have claimed that this blood has clotted and lysed [22], our work suggests that limited activation of the extrinsic pathway occurs, and inhibition of activated factors by antithrombin III pre vents further activation of the clotting fac tors in vivo [23], In addition, high levels of thrombin-antithrombin complexes have been measured in shed mediastinal blood, indicating inhibition of activated factors [23]. This blood has been successfully rein fused to thousands of patients without the hemostatic derangements that some investi gators have suggested will occur [24,25], Nevertheless, the ability of shed mediastinal blood to contribute to hemostasis by provid ing functioning clotting factors is still in Washing, however, does not render the transfused blood totally free of potentially harmful material. Gilcher [26] has reported that washing removes bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Al though some investigators have claimed that this blood has clotted and lysed [22], our work suggests that limited activation of the extrinsic pathway occurs, and inhibition of activated factors by antithrombin III pre vents further activation of the clotting fac tors in vivo [23], In addition, high levels of thrombin-antithrombin complexes have been measured in shed mediastinal blood, indicating inhibition of activated factors [23]. This blood has been successfully rein fused to thousands of patients without the hemostatic derangements that some investi gators have suggested will occur [24,25], Nevertheless, the ability of shed mediastinal blood to contribute to hemostasis by provid ing functioning clotting factors is still in Washing, however, does not render the transfused blood totally free of potentially harmful material. Gilcher [26] has reported that washing removes bacteria.…”
mentioning
confidence: 99%
“…The presence of coagulopathies in some patients who have received autologous blood transfusion has led some investigators to question the possible contribution of au tologous transfusion to these derangements in the clotting mechanism [20,25,28]. We feel that these coagulopathies are usually related to dilutional factors associated with massive blood replacement, or to the hemo static derangements associated with the mul tiple injuries in these patients [29], Another area currently being investigated is the immunologic competence of shed blood.…”
mentioning
confidence: 99%
“…134 Complications of intraoperative salvage are surprisingly infrequent. 139,140 In general, this clinical picture is related to a combination of the characteristics of the salvaged blood and hemodilution in the recipient. 135 Free hemoglobin levels may exceed 1000 mg/dL, and in the recipient this can result in hemoglobinemia and hemoglobinuria (Table 30-2).…”
Section: Intraoperative Autologous Transfusion: Blood Salvagementioning
confidence: 99%
“…Extensive research has been done in people, but only limited studies exist in dogs. A literature search yields only a few case reports on the clinical use of automated cell salvage devices in canine patients and some basic science studies using dogs as an experimental model for people, focusing specifically on undesirable effects of cell salvage . For this reason, a prospective investigation of the effects of processing canine blood with an automated cell salvage device was warranted.…”
Section: Introductionmentioning
confidence: 99%